Lichens and lichenicolous fungi Kalmius department of Ukrainian Steppe Reserve (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
55 species of lichens and lichenicolous fungi on the territory of Kalmiussky department of the Ukrainian steppe reserve (Donetsk region) were found. Among them Rinodina aspersa (Borrer) J.R. Laundon is new species for Ukraine. The largest ecological group is saxicolous (32 species, 71,1 %), fewer presented lichens species growing on the soil (8, 13,5 %). The annotated list of the species are provided. This is the first study of lichens in the department.
Keywords: Rinodina aspersa, granite, Kal`mius.